Female Refugees in Rural Germany: A Local Aid Agency's Efforts to Build on Women's Experiences and Needs. - Seethaler, Ina C. (Frontiers: A Journal of Women Studies, 2019)
The article focuses on positive ways in which a small volunteer organization in rural southwest Germany, Willkommen in Wertheim, implements feminist principles to empower female refugees. It mentions social construction of gender causes differently gendered groups to experience displacement in diverse ways. It also mentions international organizations and non-governmental organization (NGOs) have adopted gender mainstreaming as a policy commitment.